A Successful Pregnancy by Utilization of Gradually Increasing Low Dose Gonadotrophin Stimulation in a Modified Natural Cycle in Vitro Fertilization Procedure: Case Report - Serkan Kahyaoğlu; Ayşe Seval Erdinç; Nafiye Karakaş Yılmaz; Mahmut Nedim Çiçek (Gynecology Obstetrics & Reproductive Medicine)
The modified natural cycle in vitro fertilization (MNC-IVF) treatment can be a promising method for poor responder patients especially in young patients with poor ovarian reserve. A 34-year-old primary infertile woman presented with a history of poor ovarian response and cycle cancellation following controlled ovarian hyperstimulation during an IVF-ET procedure two months ago. During MNC-IVF treatment with intracytoplasmic sperm injection (ICSI), gradually increasing doses of hMG for three days (totally 675 IU) have been administered accompanied by daily 0,25 mg cetrorelix. Following ovulation triggering, one oocyte was picked up and a good quality (grade 1) embryo was transferred on day 2. A clinical pregnancy was established with ultrasonography on sixth weeks of gestation. Acceptable pregnancy rates per embryo transfer, low medication cost, relatively low risk of complications and higher patient acceptability are the main advantages of MNC-IVF treatment as a feasible treatment option especially for poor responder patients.